Particulate matter exposure and chronic cerebral hypoperfusion promote oxidative stress and induce neuronal and oligodendrocyte apoptosis in male mice. Issue 3 (4th December 2022) - Lamorie‐Foote, Krista; Liu, Qinghai; Shkirkova, Kristina; Ge, Brandon; He, Shannon; Morgan, Todd E.; Mack, Wendy J.; Sioutas, Constantinos; Finch, Caleb E.; Mack, William J.
Abstract: Chronic cerebral hypoperfusion (CCH) may amplify the neurotoxicity of nanoscale particulate matter (nPM), resulting in white matter injury. This study characterized the joint effects of nPM (diameter ≤ 200 nm) and CCH secondary to bilateral carotid artery stenosis (BCAS) exposure on neuronal and white matter injury in a murine model. nPM was collected near a highway and re‐aerosolized for exposure. Ten‐week‐old C57BL/6 male mice were randomized into four groups: filtered air (FA), nPM, FA + BCAS, and nPM + BCAS. Mice were exposed to FA or nPM for 10 weeks. BCAS surgeries were performed. Markers of inflammation, oxidative stress, and apoptosis were examined. nPM + BCAS exposure increased brain hemisphere TNFα protein compared to FA. iNOS and HNE immunofluorescence were increased in the corpus callosum and cerebral cortex of nPM + BCAS mice compared to FA. While nPM exposure alone did not decrease cortical neuronal cell count, nPM decreased corpus callosum oligodendrocyte cell count. nPM exposure decreased mature oligodendrocyte cell count and increased oligodendrocyte precursor cell count in the corpus callosum. nPM + BCAS mice exhibited a 200% increase in cortical neuronal TUNEL staining and a 700% increase in corpus callosum oligodendrocyte TUNEL staining compared to FA. There was a supra‐additive interaction between nPM and BCAS on cortical neuronal TUNEL staining (2.6× the additive effects of nPM + BCAS). nPM + BCAS exposure increased apoptosis, neuroinflammation, and oxidative stress in the cerebral cortex and corpus callosum. nPM + BCAS exposure increased neuronal apoptosis above the separate responses to each exposure. However, oligodendrocytes in the corpus callosum demonstrated a greater susceptibility to the combined neurotoxic effects of nPM + BCAS exposure. Abstract : This study demonstrates that nanoparticulate matter (nPM) exposure and chronic cerebral hypoperfusion (CCH) promote oxidative stress and induce neuronal apoptosis in a synergistic manner. Oligodendrocytes are preferentially vulnerable to the toxicity of nPM exposure and CCH. nPM exposure causes mature oligodendrocyte cell death and increases the number oligodendrocyte precursor cells.